An Analysis of Students’ Collaboration Skills in Science Learning Through Inquiry and Project-Based Learning - Hairida, Hairida; Marmawi, Marmawi; Kartono, Kartono (Universitas Islam Negeri Raden Intan Lampung, 2021)
Collaboration skills are essential for students when facing the working world in 21st-century society. The study aims to determine students' collaboration skills through inquiry and project-based learning in science. The descriptive method was implemented with surveys and interviews. The participants were 175 students from Junior High School. Data collection was carried out using collaborative skill observation sheets and an interview guide. The results showed that, in general, the collaboration skills of participants were categorized as high regarding the indicators of collaboration skills. The indicators consisted of contributing to group discussions (72.57 percent), working effectively in group discussions (77.14 percent), communicating in group activities (74.86 percent), and having responsibility for completing group assignments (75 percent). Therefore, teachers are advised to apply inquiry and project-based learning in science to improve student collaboration skills.